MIGRANT HOMELESSNESS AND THE CRIMMIGRATION CONTROL SYSTEM - Serpa, Regina (ROUTLEDGE, 2023)
"Migrant Homelessness and the Crimmigration Control System offers new insights into the drivers of homelessness following migration by unpacking the housing consequences of 'crimmigration' control systems in the US and UK. The book advances 'housing sacrifice' as a concept to understand journeys in and out of homelessness and the coping strategies migrants employ. Undergirded by persuasive empirical research, it offers a compelling case for a 'social citizenship' right to housing guaranteed across social, political and civil realms of society. The book is structured around the 30 life stories of people who have migrated to the capital cities of Boston and Edinburgh from Central America and Eastern Europe. The narratives are complemented by interviews with a range of stakeholders (including frontline case workers, activists and policy makers). Guided by the tenets of critical realist theory, this book offers a biographical inquiry into the intersections of race, class and gender and provides insight into the everyday precarity homeless migrants face, by listening to them directly. It will be of interest to students, scholars, and policy makers across a range of fields including housing, immigration, criminology, sociology, and human geography"--